A new sequential model for coupling flow and geomechanics in poroelastoplastic reservoirs - Silva, Rafael de Oliveira da (2018)
We develop an innovative computational model for single phase flow of a slightly compress- ible fluid in a rock displaying elastoplastic behavior. The new geomechanical formulation revolves around the fixed stress split algorithm within the class of sequential methods, where the subproblems of flow and geomechanics are solved in an iterative fashion for a frozen total mean stress. We show that in the general case where the Biot-Willis coeffi- cient is modified in the plastic regime, additional complexity arises in both equilibrium and flow equations. Considering the plastic flow governed by Terzaghi’s effective stress, a new nonlinear Biot-Willis parameter naturally appears in the overall equilibrium of the solid-fluid mixture. The new model is discretized by the finite element method and numerical simulations are presented considering a 2D slab arrangement representing a section between an injection and a production well. The simulations illustrate the role of the source terms, involving the time derivative of the total mean stress, in production and reservoir compaction in the plastic regime.